In-season crop yield forecasting in Africa by coupling remote sensing and crop modeling: A systematic literature review - Xiong, Wei (International Maize and Wheat Improvement Center, 2022)
Timely and accurate estimation of crop yield before harvest is crucial for national food policy and security assessments. Crop models and remote sensing techniques have been combined and applied in crop yield estimation on a regional scale. Previous studies have proposed models for estimating canopy state variables and soil properties based on remote sensing data and assimilating these estimated canopy state variables into crop models. This paper presents an overview of the comparative introduction, latest developments and applications of crop models, remote sensing techniques, and data assimilation methods in the growth status monitoring and yield estimation of crops, facilitating the improvement of crop models and RS coupling approach in Africa.